Dynamic Regulation of Ions and Amino Acids in Adult Asian Hard Clams Meretrix lusoria Upon Hyperosmotic Salinity - Lin, Chia-Hao; Yeh, Po-Ling; Wang, Yu-Chun; Lee, Tsung-Han (Frontiers in Marine Science, 2021)
The dynamic regulation of ions and amino acids in the gills and mantle of the Asian hard clam, Meretrix lusoria, following the exposure to a hyperosmotic environment was hitherto unclear. The present study revealed that the osmolality as well as the Na+ and Cl- concentrations in the hemolymph were significantly increased 3 h after transferring the clams from an environment with the salinity of their natural habitat (brackish water; BW; 20‰) to one with hyperosmotic salinity (seawater; 35‰). In addition, we found that the specific activities of Na+/K+-ATPase, a key enzyme that plays a significant role in cell osmoregulation, in the gills and mantle of clams were significantly increased at 72 and 12 h post-transfer, respectively, during acclimation to hyperosmotic salinity. Similarly, the contents of free amino acids (FAAs) such as taurine, alanine, and glycine were significantly elevated during hyperosmotic salinity acclimation. Previous research indicates that taurine is the most abundant FAA in the gills and mantles of Asian hard clams and that the taurine transporter (TAUT) plays an important role in taurine accumulation. The present study showed that TAUT mRNA and protein expression were significantly and transiently increased in the mantle of Asian hard clams following exposure to seawater; although the expression of TAUT mRNA in the gills of Asian hard clams was also transiently stimulated by exposure to hyperosmotic salinity, the relative TAUT protein abundance decreased only at later stages. Accordingly, the findings of this study improve our understanding of the dynamic processes of ion and amino acid regulation in the peripheral tissues of bivalves under hyperosmotic stress.